BIOMASS AND DENSITY OF SEAGRASS Thalassia hemprichii FROM NIRWANA BEACH WEST SUMATRA - Ayu Agustina; Zulkifli '; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Research has been conducted in the month of October-November 2015 at Nirwana Beach of West Sumatra. The aim of this study was to determine the density and biomass and habitat characteristics determine the effect of the density and biomass of seagrass Thalassia hemprichii in waters Nirwana Beach West Sumatra. Results showed the highest density of seagrass Thalassia hemprichii at Nirwana Beach West Sumatra was located on the second station in the amount of 193.98 stands/m2 and lowest density was found on the third station at 99.99 stands/m2 . Thalassia hemprichii biomass was highest at station II transect 1 with a dry weight of 13.452 g/m2 , the lowest of seagrass biomass was at transect III station 3 with a dry weight of 7.512 g/m2 .Keywords : Thalassia hemprichii , density and biomass, Nirwana Beach.